(untitled) (Web of Technology: Multidimensional Research Journal, 2024)
The article discusses the role and significance of mathematics in teaching physics. The authors emphasize the need to master the modern mathematical apparatus in order to successfully master physics. Methods of mathematical modeling of physical phenomena, including the use of differential equations, are described. Particular attention is paid to the inductive approach in the study of Maxwell’s equations and their significance in the generalization of physical laws. The concept of model-algorithm-design for analyzing and describing physical processes is also discussed.